Korelasi Status Perkawinan, Pendapatan Keluarga, Kebiasaan Makan “Muluk” dan Konsumsi Gorengan terhadap Risiko Diabetes pada Wanita Lansia Awal (46-55 Tahun) - Sari, Dhian Kartika; Kharisma Wardani, Iing Meillarosa; Masyiyah, Shofiyatul; Samah, Dea Aflah; Alma, Lucky Radita; Katmawanti, Septa; Ulfah, Nurnaningsih Herya (Preventia: The Indonesian Journal of Public Health, 2021)
The objective of this study is to analyze the relationship between marital status, family income, the habit of eating with hands ("muluk"), and fried food consumption with the risk of diabetes in early elderly women aged 46–55 years. The method used was an observational study with 83 respondents. The research instrument was a questionnaire. The results showed that 89.2% of respondents were married. It was also found that the average family income of respondents was below the Regional Minimum Wage (UMR) (62.7%). The majority of respondents reported eating with hands ("muluk") 7 times a week (27.7%), and 75.9% of respondents stated that they were more comfortable using "muluk" when eating. In addition, 33.7% admitted to regularly consuming fried foods as snacks. Regarding diabetes risk, 86.7% were in the low-risk category. The results of the chi-square bivariate test showed no relationship between marital status (p-value: 1.00), family income (p-value: 1.00), preferred eating method (p-value: 1.00), and fried food consumption (p-value: 0.319) with diabetes risk. The results of the Kendall's Tau bivariate test showed no relationship between the frequency of eating with hands ("muluk") (p-value: 0.897) and the number of fingers used for "muluk" (p-value: 0.596) with diabetes risk.